2018
DOI: 10.1245/s10434-018-6738-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Total Mesorectal Excision for Sphincter-Saving Surgery: Results of a Single-Center Series of 400 Consecutive Patients and Perspectives

Abstract: R-TME is less likely to be converted to open surgery than L-TME; operative time and curative pathologic criteria are equivalent. Future prospective trial should compare standardized procedures performed by experienced surgeons for subgroups of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…The surgical procedures were standardized for all patients and done by the same team under a single senior surgeon, with no differences between groups. The RTME technique was as described previously. ERAS management was completed according to the most recent guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical procedures were standardized for all patients and done by the same team under a single senior surgeon, with no differences between groups. The RTME technique was as described previously. ERAS management was completed according to the most recent guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The national LOS for the different surgical approaches, as well as the additional instrumentation costs, were extracted from the French National Cost Studies. To limit sample size bias, the conversion rates reported in a large 400‐patient study that had been conducted in the authors' hospital were used: 9·5 per cent for laparoscopy and 2 per cent for robot‐assisted surgical approaches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jayne et al assessed female sexual functioning with the Female Sexual Function Index (FSFI, higher scores indicating better function) and found no significant difference between scores for the laparoscopic and the RAS group at 6-month postoperatively (laparoscopy minus RAS: 1.231; CI − 3.54, 6.00; p = 0.60) [11]. Rouanet et al did not find significant differences for the FSFI or IIEF between RAS and laparoscopy but provided graphical results which were not feasible for pooling [35].…”
Section: Urinary Retentionmentioning
confidence: 99%
“…The heterogeneity was low (I 2 = 0%). In addition, Rouanet et al also found no differences between the two groups [35]. Kim et al reported no differences between laparoscopy and RAS for quality of life at 3 weeks, 3 months and 12 months [34].…”
Section: Quality Of Lifementioning
confidence: 99%